Koszty marketingu w przedsiębiorstwach świadczących usługi w sektorze business-to-business : analiza przypadków - Nowak, Marta (Marketing Costs in Business-to-Business Service Companies : Case Studies Analysis, 2006)
"Service sector differs from production sector significantly. Business-to-business services are the special kind of services. Services, especially business-to-business services, need more sophisticated marketing than material goods. Therefore the structure of marketing costs structure is different. Also marketing costs vary depending on different factors, such as the company size, type of services and :ompany's clients. "
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1101, s. 211-216